2016
DOI: 10.1002/jbm.a.35654
|View full text |Cite
|
Sign up to set email alerts
|

Current investigations into magnetic nanoparticles for biomedical applications

Abstract: It is generally recognized that nanoparticles possess unique physicochemical properties that are largely different from those of conventional materials, specifically the electromagnetic properties of magnetic nanoparticles (MNPs). These properties have attracted many researchers to launch investigations into their potential biomedical applications, which have been reviewed in this article. First, common types of MNPs were briefly introduced. Then, the biomedical applications of MNPs were reviewed in seven part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
176
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(177 citation statements)
references
References 130 publications
(231 reference statements)
1
176
0
Order By: Relevance
“…Synthetic polymers include polyethylene oxide (PEO)/polyethylene glycol (PEG), poly (vinyl alcohol) (PVA), poly (acrylic acid) (PAA), and others [49]. Implant surface with PEG and/or PEO coating can endow the ability of anti-bacteria adhesion [77, 78]. There was a report that the inclusion of arginine-glycine-aspartic acid (RGD) array restored the function of local osteoblasts that were damaged by some synthetic polymer coatings [79].…”
Section: Main Components Of Coating For Irismentioning
confidence: 99%
“…Synthetic polymers include polyethylene oxide (PEO)/polyethylene glycol (PEG), poly (vinyl alcohol) (PVA), poly (acrylic acid) (PAA), and others [49]. Implant surface with PEG and/or PEO coating can endow the ability of anti-bacteria adhesion [77, 78]. There was a report that the inclusion of arginine-glycine-aspartic acid (RGD) array restored the function of local osteoblasts that were damaged by some synthetic polymer coatings [79].…”
Section: Main Components Of Coating For Irismentioning
confidence: 99%
“…The biocompatibility and non-toxicity of magnetic colloids has led to their extensive use in the following: targeted drug delivery [1][2][3][4][5][6]; clinical diagnostics as contrast agents for magnetic resonance imaging [6][7][8][9][10]; tumor therapy by controlled hyperthermia [9][10][11][12]; cytological studies [13][14][15][16][17]; and in catheter embolization of blood vessels [18].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanomaterials have been applied in various biomedical applications, such as in cell marking and separation, targeted drug delivery, thermotherapy, and magnetic resonance contrast enhancement, and have been found to be biocompatible and suitable for pain-free microsurgery. (8)(9)(10) The noncontact motion control of magnetic nanomaterials has been investigated. Fan et al (11) observed the rotation of gold, platinum, and nickel nanowires in an alternating electric field.…”
Section: Introductionmentioning
confidence: 99%